Low-dose CT Reduces Radiation Exposure by Ninety Percent Compared to Traditional CT among Patients Undergoing Hip Preservation Surgery - Su, Alvin W. (Arthroscopy, 2019)
PURPOSE: To compare the delivered radiation dose between a low-dose hip CT (Computed Tomography) scan protocol and traditional hip CT scan protocols (referred to as: traditional CT). METHODS: This was a retrospective comparative cohort study. A group of patients who underwent hip preservation surgery (including arthroscopy, surgical hip dislocation, or periacetabular osteotomy procedures) at our institution between 2016-2017 were identified. Patients were excluded if they had a BMI>35 kg/m(2), previous surgery, or absence of a radiation dose report. The low-dose group included patients undergoing hip CT at our institution utilizing a standardized protocol of 100 kVp, 100 mAs and limited scanning field. The traditional CT group included patients who had hip CT scans performed at outside institutions. The total effective dose (E(hip)), effective dose per millimeter-body-length-scanned (E(mm)), and the patients’ age, BMI were compared by univariate analysis. The correlation of E(hip) to BMI was assessed. RESULTS: Forty-one consecutive patients were included in the low-dose group, and 18 consecutive patients were included in the traditional CT group. Low-dose CT resulted in 90% reduction in radiation exposure compared to traditional CT (E(hip)=0.97 ± 0.28 vs. 9.68 ± 6.67mSv, p<0.0001). Age (28±11 vs. 26±10 years, p=0.42), sex (83% vs. 76% female, p=0.74), and BMI (24±3 vs. 24±3 kg/m(2), p=0.75) were not different between the two groups. E(hip) had poor but significant correlation to BMI in the low-dose CT group (R(2)=0.14, slope=0.03, p=0.02), and did not correlate to BMI in the traditional CT group (R(2)=0.13, p=0.14). CONCLUSIONS: Low-dose hip CT protocol for the purpose of hip preservation surgical planning resulted in 90% reduction in radiation exposure compared to traditional CT. LEVEL OF EVIDENCE: Diagnostic Study, Level II